Leaf spot of Centrosema species caused by Cylindrocladium colhounii - Lenné, Jillian M.; Vargas de Alvarez, A. (Scientific Societies, 1990)
A previously undescribed leaf spot of Centrosema spp. in Colombia and Costa Rica was found to be caused by Cylindrocladium colhounii. Symptoms included irregular, zonate, brown leaf spots, 10–30 mm in diameter; chlorosis; and defoliation. Pastures of Centrosema acutifolium cv. Vichada in the eastern plains of Colombia were moderately to severely defoliated under humid conditions. The host range of the pathogen was restricted to C. acutifolium, C. arenarium, C. brasilianum, C. macrocarpum, and C. pubescens. Usable resistance was identified in accessions of C. acutifolium from Minas Gerais and Goias, Brazil, as well as in other Centrosema spp.